2014
DOI: 10.1111/tran.12065
|View full text |Cite
|
Sign up to set email alerts
|

What is land? Assembling a resource for global investment

Abstract: The so-called global land rush has drawn new attention to land, its uses and value. But land is a strange object. Although it is often treated as a thing and sometimes as a commodity, it is not like a mat: you cannot roll it up and take it away. To turn it to productive use requires regimes of exclusion that distinguish legitimate from illegitimate uses and users, and the inscribing of boundaries through devices such as fences, title deeds, laws, zones, regulations, landmarks and story-lines. Its very 'resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
384
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(394 citation statements)
references
References 48 publications
2
384
0
8
Order By: Relevance
“…This allows us to study the role of materiality, and how materiality enables, shapes and especially blocks innovation at times: the role of material barriers to innovation are put on equal footing with ethical/social/economic/psychological barriers to innovation that arise from the human domain. Indeed, we also draw on Tania Murray Li's (2008Li's ( , 2014 work to highlight that entities such as land figuring as a resource (or as a natural area, a 'wasted space', etc.) is not an intrinsic quality of the land.…”
Section: Family Resemblances: Insights From Related Research Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows us to study the role of materiality, and how materiality enables, shapes and especially blocks innovation at times: the role of material barriers to innovation are put on equal footing with ethical/social/economic/psychological barriers to innovation that arise from the human domain. Indeed, we also draw on Tania Murray Li's (2008Li's ( , 2014 work to highlight that entities such as land figuring as a resource (or as a natural area, a 'wasted space', etc.) is not an intrinsic quality of the land.…”
Section: Family Resemblances: Insights From Related Research Fieldsmentioning
confidence: 99%
“…It is important to learn to recognise such material barriers to innovation and to give this a place in the RI process: if these are not recognised but treated as technological problems that can be overcome using yet another set of technologies without going through the same 'RI process' for those problem-solving technologies, one can no longer say one is doing RI. Using actor-network's symmetrical approach to humans and non-humans is a valuable starting point to theorise this, and could be combined with Li's (2008Li's ( , 2014 understanding of contingency and assemblage, highlighting that an entity's characteristics are not inherent qualities but arise from the assemblage that constitutes it. The practical experience portrayed in studies reflecting on attempts by corporations to carry out BoP projects may be a source of inspiration for dealing with a range of barriers to innovation as well, as these studies exemplify that assemblages of entities rather than single factors condition the opportunities for successful social innovation (Latour 2005;Andersen and Esbjerg 2012).…”
Section: Materials Barriers To Innovationmentioning
confidence: 99%
“…Though Castree (2010 p1734) once observed that "few critical geographers have so far used Foucault's work on "governmentality" to examine the neoliberalisation of nature", there is now a budding literature in this area using governmentality, sometimes reframed as "environmentality" following Arun Agrawal (e.g. Fletcher, 2010Li, 2007Li, , 2014Lövbrand and Stripple, 2011;Stephan, 2013;McGregor et al, 2015). This paper contributes to this body of work by recovering Foucault's reading of neoliberalism as a specific rationality, integrating this with a general understanding of governmentality as dispositif or apparatus -aspects that are often treated separately in environmental governmentality literature.…”
Section: Introductionmentioning
confidence: 99%
“…This international land grab literature overwhelmingly focuses on large-scale land transformationon a new scale and with a new intensity-resulting from processes of globalisation, the liberalisation of land markets, and increases in foreign direct investment in land (Deininger 2003;Sikor and Müller 2009;Borras and Franco 2010;Zoomers 2010: 130;Li 2014). In this literature, land is grabbed not only by high-wealth individuals but also by foreign governments demanding a supply of cheap food crops or arable land on which to grow biofuels and non-food agricultural crops (Cotula et al 2008(Cotula et al , 2009Borras and Franco 2010;Zoomers 2010).…”
Section: Introductionmentioning
confidence: 99%